2012
DOI: 10.1007/978-3-642-33161-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Emergency Management by a Loosely Coupled Logistic System

Abstract: We investigate a robust and intelligent logistic system for emergency management where existing commercial logistic systems are loosely coupled with logistic systems of emergency management organizations and armed forces. This system is used to supply the population in case of a disaster where a high impact of environmental conditions on logistics can be seen. Very important are robustness as the ability of a logistic system to remain effective under these conditions and intelligent behavior for automated ad-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This unstructured information is prepared by removing specific characters and tags and by correcting typographical errors [9]. Tokenization is used to separate the different terms and all terms are converted in lower case [10], [11]. The number of terms is reduced by part-of-speech tagging, by stop word filtering, by stemming, and by applying Zipf distribution.…”
Section: Methodsmentioning
confidence: 99%
“…This unstructured information is prepared by removing specific characters and tags and by correcting typographical errors [9]. Tokenization is used to separate the different terms and all terms are converted in lower case [10], [11]. The number of terms is reduced by part-of-speech tagging, by stop word filtering, by stemming, and by applying Zipf distribution.…”
Section: Methodsmentioning
confidence: 99%
“…national and industrial levels) and they mainly focus on monitoring and analyzing alternative future changes (Amer et al, 2016;Cagnin and Könnölä, 2014;Geum et al, 2014;Hey, 2012;Jovane et al, 2003;Kajikawa et al, 2011;Kikuchi et al, 2014;Pagani, 2009;Saritas and Aylen, 2010;Thorleuchter et al, 2012), as shown in Table 2. Moreover, scenario planning is strong in regard to building scenarios with a macro view of future changes, while technology roadmapping is strong for the development of roadmaps with a micro view for action planning (Geum et al, 2014;Lee et al, 2015a).…”
Section: Macro-level Scenario-based Roadmapping Approachmentioning
confidence: 99%
“…A five-step methodology was developed by using various qualitative techniques (i.e. scenario, roadmap and surveys) to identify existing challenges for emergency management and forecasting the future development of loosely coupled logistic systems in the logistics industry (Thorleuchter et al, 2012). A system roadmap of the future of logistics over 20 years containing a timetable and recommendations for government and companies was developed by human experts.…”
Section: Scenario-based Roadmappingmentioning
confidence: 99%
“…Different filtering methods are applied (Thorleuchter, Schulze, & Van den Poel, 2012): Part-of-speech tagging is used to identify the syntactic category of each term (e.g. nouns and verbs) and based on the category, non-informative terms are identified.…”
Section: Pre-processingmentioning
confidence: 99%